Two Proofs Of The Unique Self-Differentiation Property of CexCe^x

Ever since I learned elementary calculus, I have been wondering about the proof of the unique self-differentiation of CexCe^x, CC a constant. One of the proofs below I was led to by a calculus textbook; another I figured out by myself.

11: Using the Mean Value Theorem

Let f(x)f(x) be a function so that f(x)=f(x)f(x)=f'(x). Define a new function

g(x)=f(x)ex(1)g(x)=\frac{f(x)}{e^x} (1)

Now, find g(x)g'(x):

g(x)=exf(x)exf(x)e2xg'(x)=\frac{e^xf'(x)-e^xf(x)}{e^{2x}}

g(x)=ex(f(x)f(x))e2xg'(x)=\frac{e^x(f'(x)-f(x))}{e^{2x}}

But our base assumption is that f(x)=f(x)f(x)=f'(x), or that f(x)f(x)=0f'(x)-f(x)=0. In other words,

g(x)=0g'(x)=0

Now, the Mean Value Theorem implies that only constant functions have zero derivative. This means that g(x)=Cg(x)=C for some constant CC. Plugging this into (1)(1) yields:

C=f(x)exC=\frac{f(x)}{e^x}

f(x)=Cexf(x)=Ce^x


22: Using the Taylor Expansion of exe^x

Note: I would like to thank Alexander Gibson for pointing out that this proof only applies to the set of analytic functions.

Once again, let f(x)f(x) be a function so that f(x)=f(x)f(x)=f'(x). Notice that this implies the following:

f(x)=f(x)=f(x)=...=f(n)(x)f(x)=f'(x)=f''(x)=...=f^{(n)}(x)

because

f(x)=f(x)    limh0f(x+h)f(x)h=limh0f(x+h)f(x)h    f(x)=f(x)f(x)=f'(x)\implies\lim_{h\to 0} \frac{f(x+h)-f(x)}{h}=\lim_{h\to 0} \frac{f'(x+h)-f'(x)}{h}\implies f'(x)=f''(x)

and so forth. We can also say that

f(a)=f(a)=f(a)=...=f(n)(a)=Cf(a)=f'(a)=f''(a)=...=f^{(n)}(a)=C

for some constant CC. Use the theory of Taylor series to expand f(x)f(x):

f(x)=f(a)+f(a)(xa)+f(a)(xa)22!+...+f(n)(a)(xa)nn!+...f(x)=f(a)+f'(a)(x-a)+f''(a)\frac{(x-a)^2}{2!}+...+f^{(n)}(a)\frac{(x-a)^n}{n!}+...

for f(x)f(x) around any point x=ax=a. Inputting our initial assumption into the Taylor expansion of f(x)f(x) yields:

f(x)=C+C(x)+C(xa)22!+...+C(xa)nn!+...f(x)=C+C(x)+C\frac{(x-a)^2}{2!}+...+C\frac{(x-a)^n}{n!}+...

Divide both sides by CC:

f(x)C=1+(xa)+(xa)22!+...+(xa)nn!+...\frac{f(x)}{C}=1+(x-a)+\frac{(x-a)^2}{2!}+...+\frac{(x-a)^n}{n!}+...

Notice that the right hand side is the Taylor expansion of exe^x about a point x=ax=a. We can conclude that

f(x)C=ex\frac{f(x)}{C}=e^x

f(x)=Cexf(x)=Ce^x

Note: It was okay to assume that the Taylor series converges, because it always does in a small interval about xax-a.

Whew! That was a lot of theory. If you want to share your own proof of the unique self-differentiation property of CexCe^x, then share it down below in the comments.

#Calculus

Note by Andrei Li
2 years, 10 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Here is a derivation for Euler's number, based on the self-differentiation property. This is a less ambitious derivation than the one posted in the note. It doesn't attempt to prove the uniqueness of the self-differentiation property.

Suppose the following is true for some constant AA over all xx.

ddxAx=Ax\large{\frac{d}{dx} A^x = A^x}

Evaluate the difference quotient:

ddxAx=Ax+dxAxdx=AxAdx1=dxA=(1+dx)1/dx\large{\frac{d}{dx} A^x = \frac{A^{x + dx} - A^x}{dx} = A^x \\ A^{dx} - 1 = dx \\ A = (1 + dx)^{1/dx}}

The limit of this expression as dxdx approaches zero is Euler's number.

Steven Chase - 2 years, 10 months ago

Log in to reply

It's a clever proof! Not what I was expecting, but it's smart!

Andrei Li - 2 years, 10 months ago

Log in to reply

I was attempting something less ambitious (simply a derivation of Euler's number). I have made notes explaining that.

Steven Chase - 2 years, 10 months ago

Log in to reply

@Steven Chase Okay! No problem. ;)

Andrei Li - 2 years, 10 months ago

y=dydxy = \frac{dy}{dx}

1ydy=dx\frac{1}{y}dy = dx

1ydy=dx\int \frac{1}{y}dy = \int dx

lny=x+C1\ln y = x + C_1

elny=ex+C1e^{\ln y} = e^{x + C_1}

y=exeC1y = e^{x}e^{C_1}

y=Cexy = Ce^x

David Vreken - 2 years, 10 months ago

Log in to reply

Toke dey ke? lol.

Arkajyoti Banerjee - 2 years, 10 months ago

The second proof doesn't necessarily follow, you've assumed the taylor series of f(x) converges, or in other words, that f(x) is what's called analytic.Some functions can be infinitely differentiable(called smooth) and still not be analytic, for instance e^(-1/x), which has all its derivatives at 0 equal to 0, and yet it eventually grows to be much bigger than 0.

However, luckily, in complex analysis, this distinction completely dissolves, and it turns out that even if just one derivative exists, the entire function is analytic, which is just one example of why everything is better in the complex case.

Alexander Gibson - 2 years, 10 months ago

Log in to reply

Thank you for your advice! I have generalized my proof for any interval about aa, where aa is any point along the xx-axis.

Andrei Li - 2 years, 10 months ago

Log in to reply

Nope, not even that works, some dastardly functions are not analytic no matter where they are centered around

Alexander Gibson - 2 years, 10 months ago

Log in to reply

@Alexander Gibson (https://en.wikipedia.org/wiki/Non-analyticsmoothfunction)

Alexander Gibson - 2 years, 10 months ago

Log in to reply

@Alexander Gibson Thank you for your advice! I have now included a note that this proof only works for analytic functions.

Andrei Li - 2 years, 9 months ago

Isn't the first proof some sort of a circular argument?

Rahul Sethi - 2 years ago
×

Problem Loading...

Note Loading...

Set Loading...